Capacity Building in Climate Change for forest Stakeholders in India - Singh, Tajinder P.; Rawat, Vijay R. S. (Indian Forester, 2013)
The concept of Reducing Emissions from Deforestation and Degradation, along with conservation and enhancement of carbon stocks, collectively known as REDD+ speaks of incentivizing developing countries for their forestry based climate change mitigation actions. It has been decided by the UNFCCC that the REDD+ activities should be implemented in phased manner beginning with the development of national strategies or action plans, policies and measures, and capacity-building, followed by the implementation at national level. Capacity building programmes in various aspects of climate change mechanisms are required for enhancing the capabilities of forestry professionals and other stakeholders at national, state and local levels. Strengthening local community institutions through 'Gram Sabhas'. Building a cadre of rural youth, strengthening forest departments and other partner agencies have been suggested for an all inclusive approach in climate programmes and projects.